Submission of proposal by BUCG for the management fee for the MEP packages work co-ordination - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the submission of proposal by BUCG for the management fee for the MEP packages work co-ordination of BRACU new campus project site.